Diálogo creativo : hablar para pensar en el aula - Fisher, Robert, 1943-; Manzano Bernárdez, Pablo (Madrid : Ediciones Morata, 2013)
'Creative Dialogue' is an essential guide to dialogic learning, presenting practical ways of teaching children to be more thoughtful and creative and to learn more effectively through speaking and listening in school and at home.
La psicodinámica de la relación de pareja : la teoría de las relaciones objetales -- La psicodinámica de la relación de pareja : psicología del self, intersubjetividad y teoría del apego -- La reflexión sistémica sobre la pareja -- ¿Y qué hay del amor? -- La evaluación -- La técnica -- El proceso terapéutico -- La dinámica de la exposición de los problemas -- Epílogo : La supervivencia del terapeuta de pareja.
Translation of: Creative dialogue : talk for thinking in the classroom. New York : Routledge, 2009.
Includes bibliographical references (pages [273]-275).
Online resource; title from ePub and PDF title page (Digitalia, viewed June 2, 2014)
Keywords: Communication in education; Verbal behavior; Teacher-student relationships; Creative teaching; Thought and thinking; Electronic books